Pengaruh Perceived Quality dan Kelengkapan Produk Terhadap Minat Konsumen Tiyang Paran Cell Sangatta - Putri Istiqomah; Imrona Hayati; Ajis Supangat (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study analyzes the influence of perceived service quality and product completeness on consumer interest in Tiyang Paran Cell Sangatta, a local communications and financial services provider. Facing intense competition, it is crucial to understand the factors that drive consumer interest. Using a quantitative approach, data were collected through questionnaires from 31 respondents and analyzed using multiple linear regression. The results show a strong correlation (R=0.849) between the two independent variables and consumer interest. The coefficient of determination of 72% (72%) confirms that perceived quality and product completeness significantly influence consumer interest, while the remaining 28% is influenced by other factors. These findings emphasize that to increase competitiveness, Tiyang Paran Cell must continue to improve their service quality and product completeness.